Disturbances of sensation occasioned by experimental arrest of blood flow - Alfred Auersperg; Orlando Aidar; Eros A. Erhart (Arquivos de Neuro-Psiquiatria)
Disturbances of sensation in the hand were studied during and after experimental arrest of circulation to the arm. Blockage of circulation was performed as outlined by Lewis and Pochin, by putting the cuff of a sphygmomanometer on the upper arm and bringing the pressure rapidly up to 200 mm/Hg. The experiments listed below were intended to demonstrate the variability of a central reaction brought about by fairly definite disturbances of the ischaemic periphery. All experiments were made on the present writers and repeated on nine other subjects, none of whom had systolic pressure reaching 150 mm/Hg. I - Blockage of circulation in both arms led to symmetrical phenomena in both hands (thermal paresthesias, tingling and hyposthesia), both under symmetrical experimental circumstances, and under the following variations: So long as the cuff pressure on both arms was above the systolic blood pressure, differences as great as 300 mm/Hg in one cuff and 150 mm in the other did not alter the symmetry of the effects. Neither was symmetry and synchronism of paresthesias affected when compression on one side preceded equal compression on the other up to 20 seconds. II - When a punctate pressure is applied to the paresthetic field the paresthesias disappear around that point and the latter is clearly brought out from the indifferent background produced in the area of depressed skin. On the basis of Kugelberg's findings, it seems that this occurs because the impulses caused by pressure have a higher frequency and substitute the spontaneous abnormal discharges of the ischaemic nerve fibers. III - Repeated mechanical stimulation of a fingertip during the experiment failed to show any influence on sensory (touch) thresholds, in contrast, therefore, to what would be expected on the basis of the physiologic experiments which show rapid fatigue of ischaemic structures. IV - In contrast to what might be expected from the intense changes undergone by receptors in the muscles during ischaemia, as observed by Matthews, weight discrimination and the capability of hitting targets with objects of different weights were not significantly altered, even during the painful phase of fatigue. V - A nervus digitalis volaris proprius was stimulated with A.C. current of 60 cycles at a just tolerable intensity. After three minutes of stimulation the initial paresthesias and pain had almost disappeared, and were followed by numbness and increased sensory thresholds in the field of distribution of that nerve. A few seconds after stimulation was interrupted, sensation was again normal in that field. Comparable phenomena were observed under normal conditions, in the absence of ischaemia. VI - Novocaine block of a finger in the ischaemic side did not influence "pins and needles", which appear after arrest of circulation is released. Therefore, the field of origin of the "pins and needles" does not seem to be the receptor field (Weddell and Sinclair) but more probably the nerve fibers themselves (Lewis, Kugelberg). VII - As is well known, "pins and needles" are accentuated by tapping the fingers and, much less, by pressing them. Thermic and painful stimulation have no effect on these paresthesias. Tapping would probably stimulate muscle and touch receptors. On the basis of our observations and Kugelberg's physiological analysis, we are inclined to consider the nerve fibers of these receptors as the field of origin of these paresthesias. VIII - No accentuation of "pins and needles" was found by (a) tapping an anesthetized finger, nor (b) pressing the muscles; but (c) tapping the fingers does reinforce these paresthesias, also during the phase when simple pressure has the opposite effect of extinguishing them. So, it seems that accentuation is related to specific nerve fibers, but it is only brought about when a special function is at play. Therefore, enhancement of those paresthesias is limited to the correlated function of proprioceptors and touch receptors when indicating the moment of encountering an object. The following conclusions drawn from these observations seem to show the variability of central sensory reactions to experimental disturbances of the ischaemic periphery. Hyposthesias and paresthesias observed in an ischaemic limb are specially intense at the fingertips and behave, therefore, according to the type of predilection of most focal disturbances in the sensory sphere of the nervous system. This shows that the structures that are best supplied with afferent nerve fibers have no greater capacity to compensate for limited disturbances but are, on the contrary, the most vulnerable substrata of function. On the basis of Kugelberg's analysis of spontaneous impulses in ischaemic nerve fibers it seems to us that the coordinated afferent impulses resulting from a stimulus are related to exteroceptive functions, whereas the spurious irregular impulses give rise to the interoceptive representation of the abnormal status of the ischaemic hand (II). The symetry and synchronism of paresthesias and numbness (referred to in I) indicate that the interoceptive representation of the abnormal hand, as well as the disturbances of sensation to external stimuli, do not follow exactly the ischaemic disturbances in the periphery; on the contrary, they seem to develop in an autonomous order of predilective type. This independency of the reaction from the causative disturbance make numbness and the dysesthetic changes comparable to interoceptive pain and tenderness of visceral origin. Besides the change in the type of reaction, our observations show also the following compensations and modifications of the exteroceptive functions, in correlation with a partial incoordination of the afferent impulses: lack of lability of thresholds as demonstrated by continous stimulation of the sense of touch (III) and stimulation of the muscle receptors (IV) ; development of numbness and hypos-thesia on continous faradic stimulation of a nervus digitalis proprius (V). To identify the functional substratum affected under ischaemic conditions, the effect of certain stimuli on the paresthesias was observed, and these were correlated to Kugelberg's physiologic findings (II and VII). Going beyond Kugelberg's conclusions our findings seem to indicate that not only specific fibers as such, but only specific fibers under specific functional conditions can modify the paresthesias. The type of reaction is the factor that transforms an anatomic substratum to a functional one. In itself, this statement, is not contrary to the classical concept. In classical studies of reflexes, for instance, estimation of quantitative relation between stimulus and effect depends on a previous "adjustment" producing a constant functional substratum (pattern). However in ischaemic experiments, as ours have shown, one is not dealing with a constant type of reaction, but with one of a changeable nature; function and effects of stimulation influenced by central factors should always be taken into consideration in the light of that variability, so that deductions of parallelistic nature may be avoided.